Study of Positioning Effect of Arrester Before and After FCO Next to Distribution Transformer Againts Lightning Surge Strikes - Maulasa, Romi; Kurnianto, Rudi; Gani, Usman A. (Faculty of Engineering, Universitas Tanjungpura, 2024)
There are 2 methods of placing the Arrester and Fuse Cut Out (FCO) as protection at distribution substation, namely the placement of the Arrester before the Fuse Cut Out (FCO) and the placement of the Arrester after the Fuse Cut Out (FCO). Each method has a different impact in overcoming the coming lightning implosion voltage disturbance. The purpose of this study is to determine the effect of arrester placement before and after FCO on distribution transformers on lightning surge interference, and to find out how the performance of arresters and FCO when lightning surge interference occurs. In this study there are three calculations, namely the calculation of the arrester placement before the FCO, the calculation of the arrester placement after the FCO and the calculation of the maximum protection distance of the lightning arrester with the transformer. The results of this study are the placement of the Arrester before the FCO, the surge voltage that passes to the primary side of the transformer is 53,8567 kV/ µs, this value is still below the transformer TID of 125 kV. Then in the Arrester placement after the FCO the surge voltage that passes to the primary side of the transformer is 58 kV/ µs, this value is still below the TID of the transformer of 125 kV. The maximum distance of arrester placement to the transformer is 14,1 m. The conclusion of this research is that the arrester works optimally in the two placements as for FCO does not work well in the Arrester placement after FCO.